The impact of physical activity and dietary behavior on depression in college students: a study on mediation effects and network analysis - Zhang, Wen; Huang, Wenying; Hu, Chang; Yuan, Yuqing; Chen, Xinyi (Frontiers in Public Health, 2025)
ObjectivesThis study investigates the relationships between physical activity, dietary behavior, and depressive symptoms among college students, focusing on the mediating role of dietary behavior and interconnections revealed by network analysis.MethodsWe utilized convenience sampling to recruit 2,487 college students from five universities in Jiangxi Province, China. Data were collected through an online questionnaire. Physical activity levels were gauged through a brief inquiry, dietary behavior was evaluated using the College Students’ Dietary Health Literacy Questionnaire, and depressive symptoms were quantified using a widely recognised scale from the Centre for Epidemiological Studies (CES-D). Descriptive statistical analysis was conducted using SPSS 26.0, mediation analysis using PROCESS version 3.5, and network analysis using the R programming language.ResultsA significant negative correlation was found between physical activity and depression (β = −0.15, p < 0.001), with a comparable pattern observed for dietary behavior (β = −0.49, p < 0.001). Dietary behavior served as a partial mediator in linking physical activity to depression, explaining 65% of the overall impact (β = 0.28, 95% CI = [0.31, 0.25]). Network analysis results indicated that three nodes, Y6, Y10, and Y15, were centrally positioned within the network. The bridge expected influence showed that physical activity was strongly associated with dietary behavior and depression clusters.ConclusionThe findings highlight significant interconnections between physical activity, dietary behavior, and depressive symptoms. The partial mediating effect of dietary behavior underscores its importance in the relationship between physical activity and depressive symptoms. These results suggest that interventions targeting both physical activity and dietary behavior could positively impact depressive symptoms in college students, offering valuable insights for preventing and managing depression in this population.